Electron and proton peak intensities as observed by a five-spacecraft fleet in solar cycle 25 - Farwa, G. U.; Dresing, N.; Gieseler, J.; Vuorinen, L.; Richardson, I. G.; Palmroos, C.; Valkila, S.; Heber, B.; Jensen, S.; Kuehl, P.; Rodriguez-Garcia, L.; Vainio, R. (EDP SCIENCES S A, 2026)
Context. Solar energetic particle (SEP) events are related to solar flares and fast coronal mass ejections (CMEs). In the case of large events, which are typically associated with both a strong flare and a fast CME driving a shock front, identification of the dominant SEP acceleration mechanism is challenging.
Aims. Using novel spacecraft observations of strong SEP events detected in solar cycle 25, we aim to identify the parent acceleration region of the observed electron and proton events.
Methods. We analysed 45 SEP events in November 2020 - May 2023 including > 25 MeV protons using data from multiple spacecraft, including Solar Orbiter, near-Earth spacecraft (SOHO and Wind), STEREO A, BepiColombo, and Parker Solar Probe. We used peak intensities of 25-40 MeV protons and similar to 100 keV and 1 MeV electrons provided by the SERPENTINE multi-spacecraft SEP event catalogue, and studied the correlations between these peak intensities as well as with the intensity of a soft-X-ray flare associated with the SEP event. We also separated the events into those well connected and those poorly connected to the flare by the interplanetary magnetic field.
Results. We find significant correlations between electron and proton peak intensities. While events detected by poorly connected observers show a single population of events, consistent with the idea that these particles are all accelerated by a spatially extended CME-driven shock, events observed in well-connected regions show two populations. One of these populations presents higher proton peak intensities that correlate with electron peak intensities, similarly to the poorly connected events. The other population shows low proton intensities that are less well correlated with electron peak intensities. Based on our findings, we propose that the latter population is a mixture of flare- and shock-accelerated events.
Conclusions. Although this study focuses on relatively energetic SEP events including > 25 MeV protons often attributed to acceleration by CME-driven shocks, we find clear indications of a flare contribution to both electron and proton fluxes in those events originating in sectors magnetically well connected to the source region.